Studi Ekspositori Terhadap Matius 6:25-34 Dan Refleksinya Bagi Orang Percaya Dalam Mengatasi Kekuatiran - Restu Gulo (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
This article discusses the teachings of the Lord Jesus about worry according to the Gospel of Matthew 6:25-34 and its reflections for believers in overcoming worry. Worry is a person,s implicit denial of the power and promises of God. The results of the research show that to overcome worry, believers must realize these three things, namely: One, that worry is useless. Two, worry only makes the situation worse for those who eperience it. Third, keep believing in God’s care for his people by proritizing God in everything. The research method used in writing this article is a qualitative method with an expository approach. The final conclusion of the author is The writer's final conclusion is that the teachings of Jesus in Matthew 6:25-34 are very useful in helping believers overcome anxiety.